'Le Zèbre'/'Zebra', a story by Mouloud Mammeri. (1st March 2014) - Boudraa, Nabil; García, Kay (Kayla) S.
'Zebra' is a translation of 'Le Zèbre', a short story written by the Francophone Algerian writer Mouloud Mammeri. Even though it was written in 1957, this story is more relevant now than ever. It perfectly describes the plight of Algeria under French colonialism, and the suffering that has persisted even after independence. The violence of the 'black decade' of the 1990s and the Kabyle uprisings of the 2000s are evidence of a continuing crisis. The protagonist of 'Zebra' represents the quintessence of Maghrebian society torn between tradition and modernity, between past and present, between oral and written traditions, between religion and democracy. In his desperate search for authentic identity, the protagonist is rejected by the Egyptians, imprisoned by the French, accused of spying by the English, and abused by his own compatriots. Mammeri's story helps us to make sense of the tumultuous history of this region as well as to better understand the roots of the devastating experience of marginalization, a condition that has plagued his native Berber culture for centuries.'Zebra' est la traduction en anglais de la nouvelle 'Le zèbre', de l'écrivain algérien, Mouloud Mammeri. Même si cette histoire est écrite en 1957, elle est plus que jamais pertinente aujourd'hui. Elle décrit si bien le contexte d'une Algérie sous le colonialisme français mais qui souffre toujours de ses malheurs même après l'indépendance. La violence de la décennie noire des années 1990 ainsi que les révoltes en Kabylie des années 2000 témoignent justement de cette situation de crise. 'Le Zèbre' est la quintessence même de la société maghrébine, tiraillée entre la tradition et la modernité, entre le présent et le passé, entre l'écriture et l'oralité, et entre la religion et la démocratie. Le protagoniste de cette histoire, en recherche de sa vraie identité, se voit rejeté par les Egyptiens, emprisonné par les Français, soupçonné par les Anglais, et enfin maltraité par ses propres compatriotes. Cette nouvelle de Mouloud Mammeri nous permet ainsi de mieux comprendre les soubassements de ce phénomène de marginalisation qui ravage sa culture berbère depuis plusieurs siècles.